The new regulatory framework for basic sanitation and the right to access to water - Gadelha, Hugo Sarmento (2021)
This article makes a brief study of the importance of the universality of policies for the implementation of access to water and basic sanitation in Brazil by analyzing Law nº 14.026/2020 of the New regulatory Framework for Basic Sanitation, which has as its main focus to promote access until 2033 through water and sanitation policy services that are provided by the public administration and private companies. Therefore, this research seeks to identify the main innovations and contradictions promoted by this law, which defends privatization by groups linked to state and municipal interests in order to avoid political and economic costs. Thus, a literature review was carried out through the methods of deductive procedure, through exploratory research using bibliographic, qualitative and documentary data. From the results obtained, it was noticed that the law has as a priority the access to universalization of drinking water and basic sanitation services, however, this law intends to destabilize the state, starting to privatize the services so that the goals are achieved and in Contrary to this, many people are unable to afford the high fees charged for services offered by private companies, as this attempt to promote water universalization must be redirected so that everyone has access to water and sanitation services regardless of income or social condition, since the use of water is consolidated as a fundamental human right, this public will have to be attended to, regardless of whether the supply service is public or private.